Late Gothic painting in the Crown of Aragon and the Hispanic kingdoms
1 online resource.
Keywords: This book aims to analyze the genesis and evolution of late Gothic painting in the Crown of Aragon and the rest of the Hispanic kingdoms, examining this phenomenon in relation to the whole context of Europe in the second half of the fifteenth century. The authors consider the influence of the Flemish primitive movement on the art produced by their Spanish colleagues, the artistic relations and interchanges with the Netherlands and other countries, and the introduction and development of the Flemish language in the Spanish lands. The book also examines altarpieces, considering topics such as changes in shape and structure and liturgical links, along with offering stylistic analyses supported by new technologies. Contributors are Joan Aliaga, Maria Antonia Argelich, Marc Ballesté, Judith Berg Sobré, Carme Berlabé, Eduardo Carrero, Ximo Company, Francesca Español, Francesc Fité, Montserrat Jardí, Nicola Jennings, Fernando Marías, Didier Martens, Isidre Puig, Nuria Ramón, Pedro José Respaldiza, Stefania Rusconi, Tina Sabater, Albert Sierra, Pilar Silva, Lluïsa Tolosa, Alberto Velasco, and Joaquín Yarza (†).